Cardiovascular complications in children and adolescents with anorexia - Izabela Pilarska; Kinga Grabska (Termedia Publishing House, 2022)
Anorexia nervosa is a major public health problem that affects people of all ages, including children. Eating disorders can lead to many complications, one of the most serious of which are heart disorders. This article aimed to discuss the large scale of anorexia among children and adolescents, the most common cardiological complications, and presentation of a practical approach to the problem. For this purpose, a comprehensive review of the literature was conducted. The described cardiological complications in anorexics are as follows: arrhythmias, mitral valve prolapse, pericardial effusion, congestive heart failure, myocardial infarction, and Takotsubo cardiomyopathy. According to existing studies, it is essential to react quickly in the event of diagnosing an eating disorder among adolescents. Observation of the patient for cardiac complications is very important for saving the health of a child with anorexia nervosa. Children with eating disorders require long-term care, involving many people like doctors, psychologists, and parents.